Urethane foam molded body
By incorporating oriented composite particles with controlled alkali metal ions in urethane foam, the product achieves enhanced thermal conductivity and heat resistance, addressing the limitations of conventional urethane foam in high-temperature applications.
Patent Information
- Application Number
- JP2023108065
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Conventional urethane foam molded products suffer from low heat resistance, leading to deterioration of physical properties such as elongation when exposed to high temperatures, limiting their application in hot vehicle components like ECUs and junction boxes, and existing solutions do not adequately address thermal conductivity and heat resistance simultaneously.
A urethane foam molded article comprising a base material with oriented composite particles containing thermally conductive expanded graphite particles and dispersed first insulating inorganic particles, where the amount of alkali metal ions in the expanded graphite is controlled between 500 ppm and 2000 ppm to prevent hydrolysis and maintain pH balance, enhancing thermal conductivity and heat resistance.
The solution provides urethane foam with improved thermal conductivity and heat resistance, suppressing polyurethane deterioration and maintaining physical properties even at high temperatures, suitable for applications requiring both heat dissipation and electrical insulation.
Smart Images

Figure 2025006980000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a urethane foam molded article having high thermal conductivity. [Background technology]
[0002] In automobiles and other vehicles, measures are taken to reduce noise generated by engines, transmissions, etc., in order to reduce noise leaking outside the vehicle or into the passenger compartment. In electric vehicles (EVs) and hybrid electric vehicles (HEVs), the driving noise of the electric powertrain, which consists of inverters, motors, gearboxes, etc., is also a target for reduction. Soundproofing materials made of foams such as polyurethane foam are used as noise countermeasures. Foams have a low thermal conductivity because they have many cells (air bubbles) inside. For this reason, if they are placed around a noise source that generates heat, heat may accumulate and cause problems.
[0003] From the viewpoint of improving the heat dissipation of a soundproofing material using a foam, for example, Patent Document 1 describes a polyurethane foam molded body in which composite particles, which are a composite of thermally conductive particles such as expanded graphite, magnetic particles, and insulating inorganic particles, are oriented and arranged in a polyurethane foam, forming a heat transfer path in the orientation direction, thereby improving the heat dissipation. The same document also describes that dispersing insulating inorganic particles separately from the composite particles in the polyurethane foam gives electrical insulation, and improves the heat dissipation and flame retardancy depending on the properties of the insulating inorganic particles. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2013 / 042611 Summary of the Invention [Problem to be solved by the invention]
[0005] However, conventional urethane foam molded bodies have a problem of low heat resistance, specifically, that physical properties such as elongation decrease when exposed to high temperatures of about 150°C. Poor heat resistance makes it difficult to apply them to parts that become hot, such as various ECUs (Electronic Control Units) and junction boxes mounted on vehicles. Patent Document 1 only evaluates the thermal conductivity and electrical insulation of the urethane foam molded body, and does not consider heat resistance.
[0006] The present disclosure has been made in view of the above circumstances, and an object of the present disclosure is to provide a urethane foam molded product having excellent thermal conductivity and heat resistance. [Means for solving the problem]
[0007] (1) In order to solve the above problems, the urethane foam molded product of the present disclosure comprises a base material made of polyurethane foam, composite particles contained in an oriented manner in the base material, and first insulating inorganic particles dispersed in the base material, the composite particles comprising thermally conductive particles and magnetic particles bonded to the surfaces of the thermally conductive particles with a binder, the thermally conductive particles comprising expanded graphite particles, and the amount of alkali metal ions contained in the expanded graphite particles is 500 ppm or more and 2000 ppm or less.
[0008] The urethane foam molded body of the present disclosure has composite particles oriented and arranged in a substrate, and first insulating inorganic particles dispersed in the substrate. The composite particles having thermally conductive particles as cores are connected in a rosary shape to form a heat transfer path in the substrate. This allows the desired thermal conductivity to be achieved. The thermally conductive particles have expanded graphite particles. The expanded graphite particles are manufactured by inserting a substance that generates gas when heated between layers of scaly graphite. When heat is applied to the expanded graphite particles, the generated gas expands the gap between the layers and forms a layer that is stable against heat and chemicals. This stable layer becomes a heat insulating layer and prevents the transfer of heat. This provides flame retardancy to the urethane foam molded body. The first insulating inorganic particles are particles of an inorganic material having insulating properties. The presence of the first insulating inorganic particles makes it difficult for the composite particles to be electrically conductive with each other, providing electrical insulation to the urethane foam molded body. In addition, when the thermal conductivity of the first insulating inorganic particles is relatively high, in addition to the heat transfer path by the composite particles, a heat transfer path by the first insulating inorganic particles is also formed. This further improves the thermal conductivity of the urethane foam molded article. Also, if the first insulating inorganic particles have flame retardancy, the flame retardancy of the urethane foam molded article is improved.
[0009] In order to solve the problem of heat resistance in urethane foam molded bodies, the present inventors have conducted extensive research focusing on the expanded graphite particles constituting the composite particles, and have found that the amount of alkali metal ions contained in the expanded graphite particles is one of the factors that reduces the heat resistance of urethane foam molded bodies. In general, expanded graphite is produced by oxidizing graphite with sulfuric acid and an oxidizing agent, and then neutralizing the acidic substances attached to the surface with a neutralizing agent. Since an alkali metal compound, ammonia, etc. are used as the neutralizing agent, if the neutralizing agent remains on the surface of the expanded graphite, it reacts with the water contained in the polyurethane foam of the base material to generate an alkaline atmosphere. It is presumed that if it is exposed to high temperatures in this state, the hydrolysis of polyurethane is promoted and deterioration progresses. In addition, in an alkaline atmosphere, the first insulating inorganic particles may dissolve.
[0010] Therefore, the amount of alkali metal ions contained in the expanded graphite particles is limited to 500 ppm or more and 2000 ppm or less. By setting the amount of alkali metal ions to 2000 ppm or less, it is possible to prevent the polyurethane foam from becoming too alkaline. This suppresses hydrolysis of the polyurethane, making it difficult for the first insulating inorganic particles to dissolve. As a result, even if the urethane foam molded body is placed under high temperatures, it is possible to suppress deterioration of the polyurethane and suppress a decrease in physical properties such as elongation. On the other hand, due to the influence of the intercalation compound of the expanded graphite particles, the raw material for producing the urethane foam molded body may become acidic, which may affect the foaming and curing reaction. Therefore, by setting the amount of alkali metal ions to 500 ppm or more, the pH balance of the raw material can be achieved, and the effect on moldability can be reduced. As a result, the urethane foam molded body of the present disclosure has excellent thermal conductivity and heat resistance.
[0011] (2) In the above-mentioned configuration, the alkali metal ion may be a sodium ion. Sodium ions are contained in hydroxides, oxides, etc. used as neutralizing agents, and have a large effect on pH. Therefore, by limiting the amount of sodium ions, it becomes easier to optimize the pH of the polyurethane foam.
[0012] (3) In any of the above configurations, the content of the composite particles may be 5% by volume or more and 50% by volume or less, based on the volume of the urethane foam molded body being 100% by volume. This configuration can provide effects such as improved thermal conductivity due to the composite particles while minimizing the effects on the foaming and curing reaction and moldability.
[0013] (4) In any of the above configurations, the content of the first insulating inorganic particles may be 5 volume % or more and 20 volume % or less, based on the volume of the urethane foam molded body being 100 volume %. This configuration can provide the effects of imparting electrical insulation and improving thermal conductivity by the first insulating inorganic particles, while minimizing the influence on the foaming and curing reaction and moldability.
[0014] (5) In any of the above configurations, the first insulating inorganic particles may have a thermal conductivity of 5 W / m K or more. With this configuration, the first insulating inorganic particles can provide an effect of improving thermal conductivity.
[0015] (6) In any of the above (1) to (4), the first insulating inorganic particles may be one or more selected from aluminum hydroxide, aluminum oxide, aluminum nitride, magnesium hydroxide, magnesium oxide, talc, calcium carbonate, clay, mica, and silica. The first insulating inorganic particles of this configuration are relatively inexpensive and easy to obtain. Among them, aluminum hydroxide, aluminum oxide, aluminum nitride, magnesium hydroxide, magnesium oxide, and talc have relatively high thermal conductivity and are therefore suitable for increasing the thermal conductivity of the urethane foam molded body.
[0016] (7) In any of the above configurations, the composite particle may have a second insulating inorganic particle bonded to the surface of the thermally conductive particle by a binder. In this configuration, the second insulating inorganic particle may be directly bonded to the surface of the thermally conductive particle serving as a core, or may be indirectly bonded via a magnetic particle. As the magnetic particle, a ferromagnetic material such as stainless steel or iron is used. Therefore, the composite particle in which the thermally conductive particle and the magnetic particle are composited has high electrical conductivity. When the second insulating inorganic particle is bonded to the composite particle in this state, even if the composite particles are oriented in a state in which they are in contact with each other, the thermally conductive particles and the magnetic particles (conductive particles) are unlikely to come into contact with each other between the adjacent composite particles. Therefore, the electrical resistance between the composite particles increases. In addition, the composite particles come into contact with each other via the second insulating inorganic particle, so that the conduction between the composite particles can be cut off. As a result, the desired electrical insulation can be achieved in the urethane foam molded body of the present disclosure. Thus, according to this configuration, in addition to high thermal conductivity and heat resistance, electrical insulation can also be imparted. Therefore, the urethane foam molded article of this configuration is also suitable for applications requiring both heat dissipation and electrical insulation, such as heat dissipation components in electronic devices.
[0017] (8) In the above configuration (7), the second insulating inorganic particles may be one or more selected from aluminum hydroxide, aluminum oxide, aluminum nitride, magnesium hydroxide, magnesium oxide, talc, calcium carbonate, clay, mica, and silica. As explained in the above configuration (6), the second insulating inorganic particles of this configuration are relatively inexpensive and easy to obtain. Among them, talc and mica are flaky and have excellent covering properties. In addition, aluminum hydroxide, aluminum oxide, aluminum nitride, magnesium hydroxide, magnesium oxide, and talc have relatively high thermal conductivity, so they are unlikely to inhibit thermal conductivity between composite particles. Effect of the Invention
[0018] In the base material of the urethane foam molded article of the present disclosure, composite particles having thermally conductive particles as cores are oriented, and first insulating inorganic particles are dispersed. The thermally conductive particles have expanded graphite particles, and the amount of alkali metal ions contained in the expanded graphite particles is 500 ppm or more and 2000 ppm or less. This allows the pH of the polyurethane foam to be adjusted to a desired range, and even if the urethane foam molded article is placed under high temperatures, it is possible to suppress deterioration of the polyurethane and suppress a decrease in physical properties such as elongation. Therefore, the urethane foam molded article of the present disclosure has excellent thermal conductivity and heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, embodiments of the urethane foam molded article of the present disclosure will be described. Note that the embodiments are not limited to the following embodiments, and various modifications and improvements that can be made by those skilled in the art can be made.
[0020] <Urethane foam molding> The urethane foam molded product of the present disclosure has a substrate made of polyurethane foam, composite particles contained and oriented in the substrate, and first insulating inorganic particles dispersed in the substrate.
[0021] [Base material] The polyurethane foam of the base material is produced from urethane foam resin raw materials such as polyisocyanate components and polyol components. The urethane foam resin raw materials may be prepared from already known raw materials such as polyols and polyisocyanates. The polyol may be appropriately selected from polyhydric hydroxy compounds, polyether polyols, polyester polyols, polymer polyols, polyether polyamines, polyester polyamines, alkylene polyols, urea-dispersed polyols, melamine-modified polyols, polycarbonate polyols, acrylic polyols, polybutadiene polyols, phenol-modified polyols, and the like. The polyisocyanate may be appropriately selected from, for example, tolylene diisocyanate, phenylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, triphenylmethane triisocyanate, polymethylene polyphenyl isocyanate, naphthalene diisocyanate, and derivatives thereof (for example, prepolymers obtained by reaction with polyols, modified polyisocyanates), and the like.
[0022] The polyurethane foam resin raw material may further contain a catalyst, a blowing agent, a foam stabilizer, a plasticizer, a crosslinking agent, a chain extender, a flame retardant, an antistatic agent, a viscosity reducer, a stabilizer, a filler, a colorant, and the like. For example, the catalyst may be an amine catalyst such as tetraethylenediamine, triethylenediamine, or dimethylethanolamine, or an organometallic catalyst such as tin laurate or tin octanoate. The blowing agent is preferably water. Other than water, examples of the foam stabilizer include methylene chloride, fluorocarbons, and CO2 gas. The foam stabilizer may be a silicone foam stabilizer, and the crosslinking agent may be triethanolamine or diethanolamine.
[0023] The shape, size, etc. of the substrate are not particularly limited and may be appropriately determined depending on the application. The composite particles contained in the substrate may be arranged with a certain regularity. For example, they may be arranged in a straight line or a curved line between one end and the other end of the urethane foam molded body (the end does not have to be 180° opposite to the one end). They may also be arranged radially from the center toward the periphery.
[0024] [Composite particles] The composite particles oriented and contained in the substrate are particles in which magnetic particles or the like are bonded to the surface of the thermally conductive particles serving as the core by a binder. The thermally conductive particles are non-magnetic particles having a relatively large thermal conductivity. In this specification, diamagnetic materials and paramagnetic materials other than ferromagnetic materials and antiferromagnetic materials are referred to as non-magnetic materials. The thermally conductive particles have expanded graphite particles. The thermally conductive particles may be single particles or aggregate particles in which a plurality of particles are integrated. Examples of the composite particles include particles in which magnetic particles or the like are bonded to the surface of expanded graphite particles, and particles in which magnetic particles or the like are bonded to the surface of aggregate particles in which expanded graphite particles and other particles are integrated. The composite particles may also include particles in which magnetic particles or the like are bonded to the surface of particles other than expanded graphite particles.
[0025] Usually, a urethane foam molded body that has been given flame retardancy has a dropping action that drops the fire and suppresses the spread of the fire even when exposed to a flame. However, if magnetic particles are blended, the dropping action is impaired, and the self-extinguishing property of the urethane foam molded body may be reduced. In the urethane foam molded body of the present disclosure, the composite particles are oriented. Therefore, the heat applied to the urethane foam molded body is easily transferred to the thermally conductive particles, and the expanded graphite particles quickly reach the expansion start temperature. This allows the flame retardant effect of the expanded graphite particles to be exerted quickly. Therefore, according to this configuration, the decrease in the self-extinguishing property of the urethane foam molded body can be suppressed, and the flame retardancy can be maintained.
[0026] The expanded graphite particles may be appropriately selected in consideration of the expansion start temperature and the expansion rate. The expansion start temperature must be higher than the heat generation temperature during molding of the urethane foam molded body, so expanded graphite particles with an expansion start temperature of 150°C or higher are suitable. The amount of alkali metal ions contained in the expanded graphite particles is 500 ppm or more and 2000 ppm or less. By setting the amount of alkali metal ions to 2000 ppm or less, it is possible to prevent the polyurethane foam from becoming too alkaline. On the other hand, by setting the amount of alkali metal ions to 500 ppm or more, a pH balance is achieved between the intercalation compound and the raw material for producing the urethane foam molded body, and the effect on moldability can be reduced.
[0027] Examples of alkali metal ions include lithium ions, sodium ions, and potassium ions. Sodium hydroxides and oxides are often used as neutralizers in the manufacturing process of expanded graphite. Therefore, limiting the amount of sodium ions makes it easier to optimize the pH of polyurethane foam. The amount of alkali metal ions contained in expanded graphite particles can be determined by immersing 2 g of expanded graphite particle powder in 50 mL of ion-exchanged water at 50°C for 2 hours and analyzing the liquid sample using ICP (inductively coupled plasma) atomic emission spectrometry. In addition, the pH of the dispersion liquid in which 2 g of expanded graphite particle powder is dispersed in 50 mL of ion-exchanged water at room temperature (20°C ± 5°C, the same below) is preferably 6 to 8.
[0028] As thermally conductive particles other than expanded graphite particles, it is recommended to use particles with a thermal conductivity of 200 W / m K or more. Examples include natural graphite, artificial graphite, carbon materials such as carbon fiber, aluminum, gold, silver, copper, and alloys using these as base materials.
[0029] The shape of the thermally conductive particles is not particularly limited as long as they can be composited with other particles such as magnetic particles. For example, various shapes such as flakes, fibers, columns, spheres, ellipsoids, and oval spheres (a pair of opposing hemispheres connected by a cylinder) can be adopted. When the thermally conductive particles have a shape other than a sphere, the contact area between the composite particles becomes large. This makes it easier to ensure a heat transfer path and increases the amount of heat transferred.
[0030] From the viewpoint of increasing the thermal conductivity, the median diameter of the thermally conductive particles is desirably 100 μm or more, and more preferably 700 μm or more. On the other hand, if the thermally conductive particles are too large, there is a risk that the molded body will become brittle due to cracks originating from the thermally conductive particles. Therefore, the median diameter of the thermally conductive particles is desirably 3000 μm or less, and more preferably 2000 μm or less. Unless otherwise specified, the median diameter in this specification refers to the value (D 50 For commercially available products, the catalog values may be used.
[0031] The magnetic particles may be any particles capable of orienting the composite particles, and are preferably, for example, ferromagnetic materials such as iron, nickel, cobalt, gadolinium, stainless steel, magnetite, maghemite, manganese zinc ferrite, barium ferrite, strontium ferrite, etc., antiferromagnetic materials such as MnO, Cr2O3, FeCl2, MnAs, etc., and alloy particles using these. Among them, iron, nickel, cobalt, and their iron-based alloys (including stainless steel) are preferable from the viewpoint of being easily available as fine particles and having high saturation magnetization. In particular, iron is relatively inexpensive and easily available, so that it can reduce manufacturing costs and is suitable for mass production.
[0032] The magnetic particles may be directly attached to the surface of the thermally conductive particles, or may be indirectly attached via the second insulating inorganic particles described later. The magnetic particles may be attached only to a part of the surface of the thermally conductive particles, or may be attached so as to cover the entire surface. The size of the magnetic particles may be appropriately determined in consideration of the size of the thermally conductive particles, the orientation of the composite particles, and the thermal conductivity between the composite particles. For example, the particle diameter of the magnetic particles is preferably 1 / 10 or less of the particle diameter of the thermally conductive particles. In this case, the "particle diameter" is the equivalent diameter of a sphere of equal volume. When the size of the magnetic particles is smaller, the saturation magnetization of the magnetic particles tends to decrease. Therefore, in order to orient the composite particles with a smaller amount of magnetic particles, it is desirable to set the median diameter of the magnetic particles to 100 nm or more. It is more preferable to set it to 1 μm or more, and even more preferable to set it to 5 μm or more.
[0033] The shape of the magnetic particles is not particularly limited. For example, when the shape of the magnetic particles is flat, the distance between adjacent thermally conductive particles is shorter than when the magnetic particles are spherical. This improves the thermal conductivity between adjacent composite particles. As a result, the thermal conductivity of the urethane foam molding is improved. In addition, when the shape of the magnetic particles is flat, the magnetic particles and the thermally conductive particles are in contact with each other on the surface. In other words, the contact area between the two particles is large. This improves the adhesive force between the magnetic particles and the thermally conductive particles. Therefore, the magnetic particles are less likely to peel off. In addition, the thermal conductivity between the magnetic particles and the thermally conductive particles is also improved. For these reasons, it is desirable to use flaky particles as the magnetic particles.
[0034] From the viewpoint of enabling the composite particles to be oriented even in a relatively weak magnetic field, the content of the magnetic particles is desirably 20% by mass or more, where the mass of the thermally conductive particles in the substrate is taken as 100% by mass. From the viewpoint of cost reduction and weight reduction, the content of the magnetic particles is desirably 130% by mass or less. It is more preferable that the content is 100% by mass or less, and more preferably 80% by mass or less.
[0035] The binder that bonds the thermally conductive particles and the magnetic particles may be appropriately selected in consideration of the adhesiveness and the effect on the foaming and curing reaction. A water-soluble polymer is preferable because it has little effect on the foaming and curing reaction and is environmentally friendly. Examples include methyl cellulose, carboxymethyl cellulose, hydroxypropyl methyl cellulose, polyvinyl alcohol, and starch. Among them, starch is preferable because it is relatively inexpensive, has high adhesion, and has excellent granulation properties.
[0036] The thermally conductive particles and the magnetic particles are conductive. Therefore, the composite particles are aligned and oriented to form a conductive path in the base material. For example, a composite particle can be formed by adhering a second insulating inorganic particle to the surface of the thermally conductive particle with a binder in addition to the magnetic particles. By doing so, even if the composite particles are oriented, the electrical resistance between adjacent composite particles can be increased or the electrical connection can be cut off. As a result, electrical insulation can be imparted to the urethane foam molded body.
[0037] The second insulating inorganic particles may be particles of an inorganic material having insulating properties, similar to the first insulating inorganic particles dispersed in the base material. Examples of the second insulating inorganic material include aluminum hydroxide, aluminum oxide, aluminum nitride, magnesium hydroxide, magnesium oxide, talc, calcium carbonate, clay, mica, and silica. One of these may be used alone, or two or more may be used in combination. Among them, talc and mica are preferable because they are flaky and have excellent covering properties. In addition, from the viewpoint of not inhibiting the thermal conductivity between the composite particles, those with a relatively high thermal conductivity may be used.
[0038] The second insulating inorganic particles may be directly bonded to the surface of the thermally conductive particles, or may be indirectly bonded via magnetic particles or the like. The second insulating inorganic particles may be bonded to only a part of the surface of the thermally conductive particles, or may be bonded to cover the entire surface. When the entire surface of the thermally conductive particles is covered with the second insulating inorganic particles, the influence of the interlayer material of the expanded graphite particles and the remaining alkali metal ions is reduced, which is preferable. From the viewpoint of increasing the electrical resistance between the composite particles and improving the electrical insulation of the urethane foam molding, it is desirable that the second insulating inorganic particles are disposed in the outermost layer of the composite particles. The binder that bonds the magnetic particles to the thermally conductive particles and the binder that bonds the insulating inorganic particles may be the same or different.
[0039] The size of the second insulating inorganic particles may be appropriately determined in consideration of the adhesiveness to the thermally conductive particles and the magnetic particles, the electrical insulation between the composite particles, and the thermal conductivity. If the second insulating inorganic particles are too large, the adhesiveness and the thermal conductivity between the composite particles are reduced. For example, the particle diameter of the second insulating inorganic particles is preferably 1 / 10 or less of the particle diameter of the thermally conductive particles. In this case, the "particle diameter" is the equivalent volume sphere diameter. In addition, the second insulating inorganic particles are adhered to the thermally conductive particles and are only a part of the composite particles. Therefore, unlike the first insulating inorganic particles described later, the contact area with the polyurethane foam of the base material is small, and the influence on the polyurethane foam is small. For this reason, the median diameter of the second insulating inorganic particles may be 1 μm or more and 20 μm or less.
[0040] The shape of the second insulating inorganic particles is not particularly limited. For example, when the shape of the second insulating inorganic particles is flat, the distance between adjacent thermally conductive particles can be shortened compared to when the shape is spherical. Therefore, the thermal conductivity between adjacent composite particles is less likely to be hindered. In addition, the contact area with the thermally conductive particles is increased, so that the second insulating inorganic particles are less likely to peel off.
[0041] The content of the composite particles may be determined taking into consideration thermal conductivity, the effect on the foaming and curing reaction of the polyurethane foam, moldability, etc. In order to achieve the desired thermal conductivity, the content of the composite particles is desirably 5% by volume or more, assuming that the volume of the urethane foam molded body is 100% by volume. It is more preferable to set it to 10% by volume or more. On the other hand, from the viewpoint of not inhibiting the foaming and curing reaction and improving moldability, it is desirably the content of the composite particles is 50% by volume or less, and it is more preferable to set it to 20% by volume or less.
[0042] [First insulating inorganic particles] The type of the first insulating inorganic particles dispersed in the base material may be the same as or different from the second insulating inorganic particles added as constituent particles of the composite particles. The shape of the first insulating inorganic particles is not particularly limited, and may be spherical or flaky. The first insulating inorganic particles may be one type or two or more types. As the first insulating inorganic particles, the above-mentioned aluminum hydroxide, aluminum oxide, aluminum nitride, magnesium hydroxide, magnesium oxide, talc, calcium carbonate, clay, mica, silica, etc. are also suitable. In addition, from the viewpoint of increasing the thermal conductivity of the urethane foam molded body, it is desirable for the thermal conductivity to be relatively large. For example, it is preferable that the thermal conductivity of the first insulating inorganic particles is 5 W / m·K or more. Among them, aluminum hydroxide is preferable because it also has flame retardancy.
[0043] The size of the first insulating inorganic particles may be appropriately determined in consideration of the electrical insulation, thermal conductivity, moldability, etc. of the polyurethane foam. If the contact area between the first insulating inorganic particles and the polyurethane foam is large, the heat resistance of the polyurethane foam may be reduced due to the influence of the first insulating inorganic particles. For example, if the first insulating inorganic particles are particles that react with water and exhibit alkalinity, they react with the water contained in the polyurethane foam to generate an alkaline atmosphere. It is presumed that if exposed to high temperatures in this state, hydrolysis of polyurethane is promoted and deterioration progresses. Therefore, from the viewpoint of reducing the influence on the polyurethane foam, it is desirable for the first insulating inorganic particles to have large-diameter particles with a median diameter of 55 μm or more and 200 μm or less. If the median diameter is 55 μm or more, the contact area with the polyurethane foam is small, and the influence on the polyurethane foam is reduced. For example, if the large-diameter particles are particles that react with water and exhibit alkalinity (alkaline inorganic particles), deterioration due to hydrolysis of polyurethane is suppressed, and even if the polyurethane foam is placed under high temperatures, physical properties such as elongation are less likely to decrease. In this specification, "particles that react with water to become alkaline" are particles that have a pH greater than 7 when 2 g of powder of the target particles is dispersed in 50 mL of ion-exchanged water at room temperature and the pH of the dispersion is measured. On the other hand, when the median diameter is 200 μm or less, the effect on moldability is small and the occurrence of cracks is suppressed. From the viewpoint of further improving moldability and physical properties in normal state, the median diameter of the large-diameter particles is preferably 150 μm or less. The first insulating inorganic particles may be composed of only large-diameter particles, or may contain particles other than large-diameter particles as long as the desired heat resistance and moldability can be realized.
[0044] Considering the effect on the foaming and curing reaction of the polyurethane foam and moldability, the content of the first insulating inorganic particles is desirably 20% by volume or less, and more desirably 15% by volume or less, when the volume of the urethane foam molded body is taken as 100% by volume. In addition, in order to obtain the desired effects such as imparting electrical insulation and improving thermal conductivity, the content is desirably 5% by volume or more, and more desirably 8% by volume or more.
[0045] <Method of manufacturing urethane foam molded body> The method for producing the urethane foam molded article of the present disclosure is not particularly limited. As a preferred embodiment of the production method, the method for producing the urethane foam molded article of the present disclosure includes a composite particle production step, a mixed raw material production step, and a foam molding step. Each step will be described below.
[0046] [Composite particle manufacturing process] This process is a process for producing composite particles by stirring a granulation raw material containing a powder of thermally conductive particles, a powder of magnetic particles, a powder of a second insulating inorganic particle blended as required, a binder, and water. The blending amounts of the powder and binder used may be appropriately adjusted in consideration of the magnetic field orientation of the composite particles, the electrical insulation and thermal conductivity of the urethane foam molding, etc.
[0047] Considering the magnetic field orientation of the composite particles, the amount of the magnetic particle powder is preferably 20 parts by mass or more relative to 100 parts by mass of the thermally conductive particle powder. On the other hand, considering the cost and weight reduction, it is preferable to set it to 130 parts by mass or less. It is more preferable to set it to 100 parts by mass or less, and even more preferable to set it to 80 parts by mass or less. The amount of the binder is preferably 2% by mass or more, when the total mass of the powder to be bonded is 100% by mass, as a necessary and sufficient amount for adhesion of the particles. On the other hand, if the binder is excessive, there is a risk of the composite particles coagulating with each other. For this reason, the amount of the binder is preferably 10% by mass or less. It is more preferable to set it to 5% by mass or less. The binder may be solid or liquid. When a water-soluble powder is used as the binder, it is preferable to add water after stirring the binder and other powder raw materials in advance. By doing so, the aggregation of the particles can be suppressed.
[0048] In the case where the granulation raw material contains a powder of the second insulating inorganic particles and the second insulating inorganic particles are disposed in the outermost layer of the composite particles, this process may include a first stirring process in which a first raw material having a powder of thermally conductive particles, a powder of magnetic particles, a binder, and water is stirred, and a second stirring process in which the powder of the second insulating inorganic particles is added to the stirred first raw material and further stirred.
[0049] [Mixed raw material manufacturing process] This step is a step of producing a mixed raw material by mixing the powder of the composite particles produced in the previous step, the powder of the first insulating inorganic particles, and a urethane foam resin raw material.
[0050] As described above, the foamed urethane resin raw material may be prepared from raw materials such as polyol, polyisocyanate, catalyst, blowing agent, and foam stabilizer. The mixed raw material may be produced, for example, by mechanically stirring a powder of composite particles, a powder of first insulating inorganic particles, and a foamed urethane resin raw material using a stirring blade or the like. In addition, the powder of composite particles and the powder of first insulating inorganic particles may be added to at least one of the two components of the foamed urethane resin raw material (polyol raw material, polyisocyanate raw material) to prepare two types of raw materials, and then the two raw materials may be mixed to produce the foamed urethane resin.
[0051] [Foam molding process] In this process, the mixed raw material produced in the previous process is injected into the cavity of a foaming mold, and foam-molded while applying a magnetic field so that the magnetic flux density in the cavity becomes approximately uniform.
[0052] The magnetic field may be formed in the direction in which the composite particles are oriented. For example, when the composite particles are oriented in a linear manner, it is desirable to form the magnetic field lines in the cavity of the foaming mold so that they are approximately parallel from one end to the other end of the cavity. In order to form such a magnetic field, for example, magnets may be placed near both sides of one end and the other end of the foaming mold so as to sandwich the foaming mold. The magnets may be permanent magnets or electromagnets. When an electromagnet is used, the magnetic field formation can be instantly switched on and off, and the strength of the magnetic field can be easily controlled. Therefore, it is easy to control the foaming molding. In addition, it is desirable that the magnetic field lines that constitute the magnetic field form a closed loop. In this way, leakage of the magnetic field lines is suppressed, and a stable magnetic field can be formed in the cavity.
[0053] In this process, the magnetic field is formed so that the magnetic flux density in the cavity is approximately uniform. For example, the difference in magnetic flux density in the cavity is preferably within ±10%. It is more preferable that it is within ±5%, and furthermore within ±3%. By forming a uniform magnetic field in the cavity of the foaming mold, uneven distribution of the composite particles can be suppressed, and a desired orientation state can be obtained. In addition, the foaming molding is preferably performed at a magnetic flux density of 150 mT or more and 350 mT or less. In this way, the composite particles in the mixed raw material can be reliably oriented. It is desirable to apply the magnetic field while the viscosity of the foamed urethane resin raw material is relatively low. If a magnetic field is applied when the foamed urethane resin raw material thickens and the foaming molding is completed to a certain extent, the composite particles are difficult to orient, and it is difficult to obtain the desired thermal conductivity. It is not necessary to apply the magnetic field for the entire time of foaming molding.
[0054] After the foam molding is completed in this step, the mold is removed to obtain the urethane foam molded article of the present disclosure. At this time, a skin layer is formed on at least one of one end and the other end of the urethane foam molded article depending on the foam molding method. The skin layer may be cut off depending on the application (or may not be cut off). EXAMPLES
[0055] Next, the present disclosure will be described more specifically with reference to examples. In the examples, urethane foam molded articles were produced using powders of expanded graphite particles having different amounts of sodium ions, and the properties of the molded articles were evaluated.
[0056] <Production of composite particles> The composite particles were produced by stirring the granulation raw material containing expanded graphite powder as the thermally conductive particles, stainless steel powder as the magnetic particles, starch powder as the binder, talc powder as the second insulating inorganic particles, and water. Four types of expanded graphite particles, A to D, with different amounts of sodium (Na) ions, were used to produce four types of composite particles. First, 1000 parts by mass of expanded graphite powder, 600 parts by mass of stainless steel powder, and 100 parts by mass of starch powder were put into a container of a high-speed stirring type mixer granulator and mixed by blade stirring, and 400 parts by mass of water were added and mixed for 1 minute. Next, 400 parts by mass of talc powder were put in and mixed for another 4 minutes. The stirring speed was 400 rpm. The obtained powder was dried to produce the composite particle powder. Details of the materials used are shown in the following (a) to (d), and the respective blending amounts are shown in Table 1 below.
[0057] (a) Thermally conductive particles Expanded graphite powder A: "EXA-50" manufactured by Fuji Graphite Industries Co., Ltd., sodium ion amount 500 ppm, pH 6, median diameter 300 μm (the same applies to expanded graphite powders B to D). The following expanded graphite powders B to D were produced by dropping a 10% by mass aqueous solution of sodium hydroxide onto the expanded graphite powder A and drying it. The pH of the expanded graphite powder was measured by dispersing 2 g of the expanded graphite powder in 50 mL of ion-exchanged water at room temperature and measuring the pH of the dispersion after 5 minutes using a glass electrode pH meter. Expanded graphite powder B: Na ion content 1000ppm, pH 7. Expanded graphite powder C: Na ion content 2000ppm, pH 8. Expanded graphite powder D: Na ion content 3500ppm, pH 10. (b) Magnetic particles Stainless steel powder: "AKT" manufactured by Mitsubishi Steel Corporation, median diameter 8.5 to 13.0 μm. (c) Binder Starch powder: "Instant Tender Gel C" manufactured by Nippon Corn Starch Co., Ltd. (d) second insulating inorganic particles Talc powder: "Microace (registered trademark) K-1" manufactured by Nippon Talc Co., Ltd., median diameter 8 μm.
[0058] <Production of urethane foam molded body> A urethane foam molded body was manufactured using the powder of the manufactured composite particles and aluminum hydroxide powder as the first insulating inorganic particles. First, 100 parts by mass of polyether polyol (manufactured by Sumika Covestro Urethane Co., Ltd., "SBU (registered trademark) Polyol 0248"), 2 parts by mass of diethylene glycol (manufactured by Mitsubishi Chemical Corporation) as a chain extender, 2 parts by mass of water as a blowing agent, 1.5 parts by mass of tetraethylenediamine catalyst (manufactured by Kao Corporation, "Kao Raiser (registered trademark) No. 31"), and 0.5 parts by mass of a silicone foam stabilizer (manufactured by Toray Dow Corning Co., Ltd., "SZ-1333") were mixed to prepare a polyol raw material. In addition, a diphenylmethane diisocyanate (MDI) modified product was prepared as a polyisocyanate raw material. The MDI modified product was produced by mixing polyether polyol (same as above) and 4,4'-diphenylmethane diisocyanate ("Millionate MT" manufactured by Tosoh Corporation) so that the isocyanate (NCO) content was 70% by mass, and reacting at 100°C for 180 minutes under nitrogen purging. Next, 80 parts by mass of composite particle powder and 60 parts by mass of aluminum hydroxide powder ("SB53" manufactured by Nippon Light Metal Co., Ltd., median diameter 55 μm, thermal conductivity 8 W / m·K) were added to 100 parts by mass of the polyol raw material and mixed to prepare a premix polyol. Next, 100 parts by mass of the premix polyol and 10 parts by mass of the polyisocyanate raw material (MDI modified product) were mixed to prepare a mixed raw material. Incidentally, 2 g of aluminum hydroxide powder was dispersed in 50 mL of ion-exchanged water at room temperature, and the pH of the dispersion after 5 minutes was measured with a glass electrode type pH meter, which was pH 8.
[0059] Then, the mixed raw material was poured into an aluminum foaming mold (cavity is a rectangular parallelepiped of length 130 mm × width 130 mm × thickness 5 mm), and the foaming mold was sealed. Then, the foaming mold was placed in a magnetic induction foaming molding device to perform foaming molding. In the cavity of the foaming mold, a uniform magnetic field was formed by magnetic lines of force that were approximately parallel from above to below. The magnetic flux density in the cavity was 200 mT, and the difference in magnetic flux density in the cavity was within ±3%. The foaming molding was performed with a magnetic field applied for the first 2 minutes, and without a magnetic field for the following 5 minutes. After the foaming molding was completed, the mold was removed to obtain a urethane foam molding. The obtained urethane foam moldings are called urethane foam moldings A to D according to the type of powder of expanded graphite particles used. The content of the composite particles in the urethane foam moldings A to D was 7.5 volume %, and the content of the first insulating inorganic particles was 12.5 volume % (the volume of the urethane foam molding is 100 volume % in each case). The urethane foam molded bodies A, B, and C are included in the concept of the urethane foam molded body of the present disclosure.
[0060] <Evaluation of urethane foam molded products> The produced urethane foam molded articles were evaluated for thermal conductivity, elongation, heat resistance, moldability, and flame retardancy. The evaluation results are summarized in Table 1 below. The evaluation methods are as follows.
[0061] [Thermal Conductivity] The thermal conductivity of the urethane foam molded body was measured using "HC-110" manufactured by Eiko Seiki Co., Ltd., which complies with the heat flow meter method of JIS A1412-2:1999.
[0062] [stretch] Five dumbbell-shaped No. 1 test pieces as specified in JIS K 6251:2017 were prepared from the urethane foam molded body, and a tensile test as specified in the same JIS was performed for each test piece at a tensile speed of 200 mm / min to calculate the elongation at break (Eb). If the elongation at break of all test pieces was 50% or more, the physical properties at normal state were evaluated as extremely good (indicated by a circle in Table 1 below), if the elongation at break of even one but not all test pieces was 50% or more, the physical properties at normal state were evaluated as good, and if the elongation at break of all test pieces was less than 50%, the physical properties at normal state were evaluated as poor.
[0063] [Heat resistance] As in the previous evaluation of elongation, a dumbbell-shaped No. 1 test piece was prepared and placed in an oven controlled at 150°C for 400 hours. After the test piece was returned to room temperature, a tensile test was performed under the same conditions as in the previous evaluation of elongation, and the elongation at break (Eb) was calculated. If the elongation at break of all test pieces was 30% or more, the heat resistance was evaluated as extremely good (shown by a circle in Table 1 below), if at least one test piece had an elongation at break of 30% or more, the heat resistance was evaluated as good (shown by a triangle in the same table), and if the elongation at break of all test pieces was less than 30%, the heat resistance was evaluated as poor (shown by an x in the same table).
[0064] [Moldability] When the urethane foam molded body was demolded after foam molding, it was visually observed whether it had been deformed or not, and when no deformation was observed in appearance, the moldability was evaluated as extremely good (indicated by a circle in Table 1 below), when only a small deformation was observed in part of the appearance, the moldability was evaluated as good (indicated by a triangle in the same table), and when the appearance was significantly deformed, the moldability was evaluated as poor.
[0065] [Flame retardant] A vertical flame test according to the UL94 standard was carried out. In the vertical flame test, the flame of a gas burner is applied to the bottom of a specimen held vertically for 10 seconds. If the burning stops within 30 seconds, the flame is applied for another 10 seconds. If the following five criteria are all met, the flame resistance is judged to be at the V-0 level. (1) The specimen does not burn for more than 10 seconds in either of the two flame applications. (2) The total burning time of each of the five specimens after two flame applications does not exceed 50 seconds. (3) None of the specimens burn up to the position of the fixing clamp. (4) None of the specimens drips burning particles that ignite the cotton placed below the specimen. (5) After the second flame application, the specimen does not continue to glow red for more than 30 seconds. If the following five criteria are all met, the flame resistance is judged to be at the V-2 level. (1) None of the specimens burn for more than 30 seconds in either of the two flame applications. (2) The total burning time of each of the five specimens after two flame applications does not exceed 250 seconds. (3) No burning specimen reaches the clamps, (4) Burning particles drip and ignite the cotton placed below the specimen, and (5) After the second exposure to flame, the specimen does not continue to glow red for more than 60 seconds.
[0066] [Table 1]
[0067] As shown in Table 1, urethane foam moldings A to C have composite particles granulated using expanded graphite powder with a sodium ion content of 500 ppm to 2000 ppm. Therefore, the elongation in the normal state was good, and the decrease in elongation was small even after being kept at high temperatures. In addition, the thermal conductivity of urethane foam moldings A to C was high, at 0.5 W / m·K or more. The sodium ion content of urethane foam molding A is smaller than that of urethane foam moldings B and C. This caused the mixed raw material to become acidic, which affected the curing reaction, leading to a decrease in moldability and flame retardancy. The sodium ion content of urethane foam molding C is larger than that of urethane foam moldings A and B. Therefore, the heat resistance was slightly decreased. From the above, it was confirmed that urethane foam moldings A to C satisfy the thermal conductivity and heat resistance. In contrast, polyurethane foam molding D, which has composite particles granulated using expanded graphite powder with a high sodium ion content of 3,500 ppm, had satisfactory thermal conductivity, normal state physical properties, and flame retardancy, but showed poor heat resistance. [Industrial Applicability]
[0068] The urethane foam molded product of the present disclosure is suitable as a soundproofing material for vehicle parts such as battery covers, electric powertrain (eAxel) covers, seat motor covers, undercovers, floor mats, dash silencers, hood silencers, various ECUs, and junction boxes, as well as for electronic devices such as personal computers.
Claims
1. The insulating layer has a base material made of polyurethane foam, composite particles contained in the base material in an oriented state, and first insulating inorganic particles dispersed in the base material, The composite particle has a thermally conductive particle and a magnetic particle bonded to a surface of the thermally conductive particle by a binder, The thermally conductive particles include expanded graphite particles, and the amount of alkali metal ions contained in the expanded graphite particles is 500 ppm or more and 2000 ppm or less.
2. The urethane foam molded article according to claim 1 , wherein the alkali metal ions include sodium ions.
3. 2. The urethane foam molded article according to claim 1, wherein a content of the composite particles is 5 volume % or more and 50 volume % or less, where the volume of the urethane foam molded article is 100 volume %.
4. The urethane foam according to claim 1 , wherein the content of the first insulating inorganic particles is 5 vol % or more and 20 vol % or less, where the volume of the urethane foam is 100 vol %.
5. The urethane foam molded article according to claim 1 , wherein the first insulating inorganic particles have a thermal conductivity of 5 W / m·K or more.
6. 2. The urethane foam molded article according to claim 1, wherein the first insulating inorganic particles comprise at least one selected from the group consisting of aluminum hydroxide, aluminum oxide, aluminum nitride, magnesium hydroxide, magnesium oxide, talc, calcium carbonate, clay, mica, and silica.
7. The urethane foam molded article according to claim 1 , wherein the composite particles have second insulating inorganic particles bonded to the surfaces of the thermally conductive particles with a binder.
8. The urethane foam molded article according to claim 7 , wherein the second insulating inorganic particles comprise at least one selected from the group consisting of aluminum hydroxide, aluminum oxide, aluminum nitride, magnesium hydroxide, magnesium oxide, talc, calcium carbonate, clay, mica, and silica.
Citation Information
Patent Citations
Urethane foam molding and method for manufacturing same
WO2013042611A1